Linkages between mitigation and adaptation in land-use change and forestry activities - Murdiyarso, Daniel; Robledo, C.; Brown, S.; Coto, O.; Drexhage, J.; Forner, C.; Kanninen, M.; Lipper, Leslie; North, N.; Rondón, Marco Antonio (Center for International Forestry Research, 2005)
This chapter explores the opportunities for linking mitigation activities with efforts to increase adaptive capacity. Because the issue involves two separate objectives, each with multiple stakeholders and scales of analysis, win-win situations are emphasised. Criteria and indicators for monitoring adaptation to climate change are discussed in the light of emerging standards for mitigation project development and monitoring.